FEATURES OF INDICATORS OF HIGH-QUALIFIED TENNIS SERVICE ACCEPTANCE AT US OPEN 2020, ATP FINAL TOURNAMENT 2020 AND AUSTRALIAN OPEN 2021 - Al Khalili, Mohaned; Stepanova, M.E. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identifying the number of indicators and the versatility of serving reception among the top eight tennis players in the world in 2020 according to the results of the rating of the Association of Tennis Professionals (ATP). Methods and structure of the study. In the course of the work, a video analysis of the Grand Slam tournaments of 2021, the Australian Open in 2021, the final championship of the ATP tour in 2020, the US Open in 2020 was used. The percentage of hitting the first serve from the first match to the last among eight leading players in the ATP ranking, in tournaments during 2020-2021. Results and conclusions. In tennis, the execution of the reception of the serve depends not only on the receiver, but also on the direction of the server's serve. Depending on the server, where he sends his serve, the receiver finds himself in different conditions, however, how the receiver sends the ball from the reception and at what speed, his position, as well as the position of the server in this draw, will depend. The surface of the tennis court also plays a huge role. The article presents the directions of feed options (feed zones: A, B, C, D, E) and varieties of classifications for receiving feed in the direction from the first square.